Enhanced Recovery After Surgery (ERAS) Protocols and Postoperative Physical Function: A Systematic Review - Smerdzyński, Mateusz; Kałwa, Natalia; Kałuża, Kinga; Pater, Michał; Strzępek, Aleksandra; Łyżwa, Julia; Frączek, Karolina; Janaszek, Agnieszka; Majchrzyk, Aleksandra; Chmurska, Agnieszka (Quality in Sport, 2026)
Enhanced Recovery After Surgery (ERAS) protocols represent a modern standard of perioperative care and an effective strategy for optimizing postoperative recovery. These protocols focus on reducing the surgical stress response, providing effective postoperative pain management and accelerating functional recovery. Increasing attention has been directed not only toward reducing the length of hospital stay but also toward improving postoperative physical function, which plays a crucial role in enabling patients to return to their normal daily activities. The aim of this study is to provide a detailed analysis of the impact of ERAS (Enhanced Recovery After Surgery) protocols on postoperative physical function in patients undergoing surgical treatment. The study aims to assess the extent to which the use of integrated, multi-step perioperative care procedures influences the rate of recovery of mobility, independence in daily activities, and overall physical performance of patients after surgery.